The Function and Social Role of Traditional Food in The Life of The Banjar Community in South Kalimantan - Yuli Apriati; Rochgiyanti Rochgiyanti; Syahlan Mattiro; Ahmad Sajidin; Nur Hikmah; Alfisyah Alfisyah (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Banjar traditional cuisine is part of a cultural heritage that originated and developed within the context of wetland ecosystems, such as rivers and swamps, which are characteristic of the South Kalimantan region. However, modernization and changes in consumption patterns have caused many local cuisines to become marginalized, especially in areas that originally depended on the natural potential of wetlands. If preservation and revitalization efforts are not immediately undertaken, this rich traditional cuisine is at risk of being lost and disconnected from the younger generation. This study aims to analyze the social function and role of traditional foods in the lives of the Banjar people in South Kalimantan. The research method used is qualitative with an ethnographic approach. This research was conducted in the city of Banjarmasin, which is known for its rich culinary traditions. In this study, data were collected from nine informants who were selected using purposive sampling. Data collection was carried out through observation, in-depth interviews with cultural practitioners, and visual documentation. The data obtained was then analyzed thematically to obtain descriptive-qualitative data related to the dynamics of traditional culinary preservation in the context of local ecology and culture. The study's results revealed that the social function and role of traditional foods can be identified through their type, raw materials, preparation methods, and meaning. The social function of traditional foods can be seen in traditional and religious events, in social relationships, and in the local economy. In addition to social functions, there are also cultural functions as symbols of identity and as a medium for passing on values from generation to generation. From the results of this study, it can be concluded that traditional foods are not only culinary delights but also have social and cultural functions in accordance with the supporting community and the surrounding environment. From this study, it can be suggested that the community and the government support preservation and revitalization efforts through collaborative and sustainable activities.